Stability and identification for rational approximation of frequency response function of unbounded soil. - Du, Xiuli (Earthquake engineering & structural dynamics.)
Exact representation of unbounded soil contains the single output single input relationship between force and displacement in the physical or transformed space. This relationship is a global convolution integral in the time domain. Rational approximation to its frequency response function (frequency domain convolution kernel) in the frequency domain, which is then realized into the time domain as a lumped parameter model or recursive formula, is an effective method to obtain the temporally local representation of unbounded soil. Stability and identification for the rational approximation are studied in this paper. A necessary and sufficient stability condition is presented based on the stability theory of linear system. A parameter identification method is further developed by directly solving a nonlinear least squares fitting problem using the hybrid genetic simplex optimization algorithm, in which the proposed stability condition as constraint is enforced by the penalty function method. The stability is thus guaranteed a priori. The infrequent and undesirable resonance phenomenon in stable system is also discussed. The proposed stability condition and identification method are verified by several dynamic soil structure interaction examples.